THE INFLUENCE OF PHYSICAL AND NONPHYSICAL WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE (A STUDY AT PT ISKANDAR INDAH PRINTING TEXTILE SURAKARTA) - Rizqiah Novitasari Toatubun (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This research was conducted at PT. Iskandar Indah Printing Textile in Surakarta. The objective of this study is to identify and analyze the influence of physical work environment on employee performance, the influence of non-physical work environment on employee performance, and the simultaneous influence of physical and non-physical work environment on employee performance. This explanatory research explains the relationship among variables. The sample of this study is 91 respondents. The data of this study were obtained from Likert-scale questionnaires and were analyzed using descriptive analysis. Finding of research indicates that physical work environment have a significant influence on employee performance, that non-physical work environment has no significant influence on employee performance, and that physical and non-physical work environment simultaneously have a significant influence on employee performance.Keywords: physical work environment, non-physical work environment, employee performance